RELATIONSHIP OF SLEEP-DISORDERED BREATHING, EMOTIONAL COMPLAINTS AND ANTROPOMETRIC MEASUREMENTS (THE RESULTS OF SCREENING SURVEY AMONG SAINT-PETERSBURG CITIZENS) - E. A. Dubinina; S. L. Korostovtseva; O. P. Rotar; E. V. Moguchaya; M. A. Boyarinova; E. P. Kolesova; A. S. Alieva; S. O. Kravchenko; N. A. Paskar; Yu. V. Sviryaev; A. N. Alyokhin; A. O. Konradi (Российский кардиологический журнал)
Aim. To assess the prevalence of sleep-disordered breathing (SDB), their relation to emotional complaints, antropometric measures and life-style factors in representative cohort of a large city inhabitants (Saint-Petersburg).Material and methods. Using structured interview and antropometric methods we studied 358 citizens of Saint-Petersburg at the age of 21-68 y.o. The presence/absence of the following were evaluated: dyssomnias, SDB (snore, breathing pauses), emotional complaints, body mass index, life-style characteristics. 21,5% of respondents could not respond definitely about the sleep breathing quality, of those mostly women (25,9% vs 14,2%; p<0,05). Finally we analyzed 281 respondents 115 men and 166 women. Results. Regular snore do confirm 29,6% men and 22,9% women. Proportional increase of snoring with the age was found only in women (r=0,21; p<0,01). Apnea episodes are reported by 14,3% respondents. Clear differences by this parameter in men and women in different ages are not found. Not depending on gender and age the snore prevalence was related to obesity markers: body mass index (r=0,26; p<0,001) and waist circumference (r=0,24; p<0,001). There was no relationship of apnea prevalence and obesity markers. There was connection between snore prevalence with sleepiness level (r=0,21, p=0,001), emotional tension (r=0,24, p<0,001) and despondency (r=0,20, p<0,01), prevalence of bruxism (r=0,18, p<0,01) and awake with the feeling of suffocation/ heaviness in the chest (r=0,17, p<0,01). Apnea prevalence correlated with typicality of fatigue after night sleep (r=0,16, p<0,01), awake with the feeling of suffocation / heaviness in the chest (r=0,17, p<0,01), and with bruxism prevalence (r=0,16, p =0,01). There was no clear evidence of SDB with lifestyle connections.Conclusion. Every fourth adult of Saint-Petersburg shows the signs of SDB, which are linked with overall sleep quality decrease, dyssomnias and emotional complaints, and with obesity values.